Increased Estradiol Levels Effect on Leptin Expression in Midluteal Endometrial Tissue of Macaca Nemestrina (Southern Pig-Tailed Macaques) - Nurhuda Sahar; Adriana Viola Miranda; Afif Rasyad; Karina Rahmaningrum; Kusmardi Kusmardi; Diyah Kristanty (Tehran University of Medical Sciences, 2021)
Objective: To measure the effect of serum estradiol (E2) levels on leptin expression in Macaca nemestrina (southern pig-tailed macaque) endometrial tissue. Materials and methods: This study used paraffin-embedded midluteal phase endometrial tissue blocks of Macaca nemestrina from previous study. Included subjects were 15 female macaques of reproductive age (8-10 years) with a previous history of producing offspring, which were divided into four groups: groups administered with 30 IU, 50 IU, and 70 IU r-FSH (intervention group), and no r-FSH (control group). The stimulation was done following GnRH agonist long protocol. Staining was done using immunohistochemistry. Leptin expression was measured using immunohistochemistry (IHC) Profiler plugin of ImageJ software and counted semi-quantitatively as Histological Score (Hscore). Results: Correlation between E2 concentration to stromal leptin expression was observed (p=0.043). Conclusion: Serum estradiol concentration is found to be correlated with leptin expression in Macaca nemestrina, suggesting a mechanism of decreasing endometrial receptivity among women undergoing controlled ovarian hyperstimulation.